The Employer's Commitment to Enable the Contractor to Complete the Work in the FIDIC Contracts: (Comparative analytical study) - Hussein, Hiwa Ali; Abdulkadir, Dana Hama Baqi (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
FIDIC Construction contracts are, generally speaking, marked by the fact that they are complex and intermingled legally, technically and administratively. This requires the mutual cooperation of all the parties concerned, mainly the employer and the contractor. In spite of the fact that the performance of the main works lies within the responsibility of the contractor, but it is necessary for the employer, as the other party to a bilateral contract, to sincerely assist the contractor and make available every piece of information which is potential to the contractor This duty is basically justified by two reasons. The first one is based on the fact that it is necessary for the employer to give due insight to the contractor so that he can make the best achievement and performance in building. The second, on the other side, is that the information is relevant to the building bases and foundations which are naturally designed to bear great fixed loads permanently, so the lack of the due information may lead to cracking, fissure and defects or even total or partial collapse or dilapidation. Consequently, it becomes an urgent need for the contractor to be assisted by the employer who must observe a two-edge duty: not to impede or obstruct the works of the contractor and to give him every possible piece of information he possesses. Finally, this duty affects the cost and time of performance. Knowingly, we have shown the importance of information obtained by the employer and how far it is potential to be revealed to the contractor.